Why Multiliteracies Pedagogy Matters in Designing Cultural-Based Materials in English Classroom - Maisa Maisa (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2023)
The current issues on new literacy have been leveraged enormously for decades. Literacy is no longer delineated as the ability to read and write a single text. It has shifted into the multi-literacies within multimodal text based. The multiliteracies pedagogy approach provides the steps for teaching and learning multiliteracies in the English education context. The article aims to describe the nature of leveraging the English language teacher's competence in designing English lessons. The research method is Design and Develop research based on multiliteracies pedagogy approach Analysis. The participants are preservice teachers grade 4 at English Education Department at Faculty of Education and Science in Cirebon Raya. The steps of collecting the data are preparing the themes of multiliteracies; grouping the participants based on their experiences; conceptualizing the local content area of multiliteracies; framing the critical issues in the content area; applying the concept to the social practice with the technology integration, and the last, publishing or presenting the product of the research. Findings indicate that the participants have produced digital cultural-based lesson plans. They also seem to have more practice in developing critical thinking skills by doing collaboration in small groups to create lesson plans critically and creatively. To settle the remarkable points of the study, multiliteracies pedagogy has gradually triggered someone to leverage their competence.